Pronunciation improvement in EFL young learners through phonics instruction. - Álvarez Rojas, Daniel Felipe; Andrade Chávez, Lilian Lucero; Beltran Herrera, Maria Andrea (Corporación Universitaria Minuto de Dios, 2016)
This is a research aiming at finding out how effective Phonics Instructions improve fifth graders pronunciation of two minimal pairs /θ/ voiceless, /ð/ voiced; /I/ short and /I:/ long. Based on the observation done during the first weeks of class at Gimnasio Fray Martín de Porres with fifth graders, we found out that one of students‟ problems in learning English was pronunciation and one useful methods in teaching pronunciation was designing and implementing Phonics Instructions activities, due to Phonics Instruction is a process that involve Multisensory approaches and Learning styles, according to MOUSTAFA (1999), Multisensory Approach or VAKT (Visual-Auditory-Kinesthetic-Tactile) implies that students learn in a smooth way the information when it is presented with different modalities. The participants of this research were 13 fifth graders from Gimnasio Fray Martín de Porres in the second semester of 2015. The method for collecting data in this research was mix research, which consists in numerical and non-numerical data. The instruments used in this research were tests (students‟ oral performance), lesson plans and artifacts. This research contained three moments. The first one was a pre-test, the second one was the implementation subdivided into four stages according to the amount of sounds contrasted and finally a third moment was a post-test.
Keywords: Phonics Activities; Multisensory Approaches; Pronunciation; Ingles-Pronunciación; Ingles; Fonética; Entonación (Fonética)